Towards an entrepreneurial university model: Evidence from the Palestine Polytechnic University - Ibrahim Mohammed Awad; Meera Kh. Salaimeh (Journal of Innovation and Entrepreneurship, 2023)
This study aims to introduce a proposed model for transforming the Palestine Polytechnic University (PPU) into an entrepreneurial university. Towards that end, a quantitative approach using statistical techniques of t test, ANOVA, Kruskal-Wallis test, and Pairwise comparisons supported by explanatory and qualitative discussions were utilized. The main findings show that the applicability of entrepreneurship at PPU was relatively fair for the aspects of the compatibility of curricula with the labor market needs, community relations and partnerships, academic exchange, entrepreneurship culture, entrepreneurial education, and university internationalization. Entrepreneurship as a policy objective was moderately acceptable for university policies and regulations, scientific research and innovation, and university leadership, but the university environment was less than moderate. The findings also show that the university leadership acknowledges the importance of achieving entrepreneurship, while they pay insufficient attention to the academic exchange. Offering other supportive funding resources can accelerate entrepreneurship. Given that, this study is likely to provide a proposed model to transform PPU into an entrepreneurial university and effectively achieve the university's pioneering vision that contributes to the university's development and presents this model to the decision makers.
Keywords: 650; Entrepreneurial education; Entrepreneurial university; Entrepreneurship; Funding; Innovation; PPU